2021
DOI: 10.1177/23779608211026145
|View full text |Cite
|
Sign up to set email alerts
|

“Can Someone as Young as You Really Feel That Much Pain?” – A Survey on How People With Fibromyalgia Experience Healthcare in Sweden

Abstract: Background Research show that fibromyalgia has low credibility in healthcare, leading to poor treatment, lack of knowledge and disinterest. Therefore, people with fibromyalgia feel frustration, fear, anxiety and disappointment. Objective: The aim of this study was to explore the experiences of people with fibromyalgia in their encounters with healthcare personnel in Sweden. Method: A cross-sectional design, where 409 people with fibromyalgia answered an anonymous online patient-reported experience measure, dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The majority of these patients had a diagnosis on the admission of LBP, headache or facial pain, cervical or neck pain, articular pain, and others. The small number of FMS diagnoses on admission may be related to some concerns, like the poor knowledge among physicians about FMS or real scepticism in the medical community regarding this syndrome and its related conditions [15][16][17]. Nevertheless, the systematic application of the 2016 ACR revised diagnostic criteria for FMS to these patients after the clinical evaluation outside the examination room highlighted a prevalence of positive criteria for FMS in 57 patients (20.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these patients had a diagnosis on the admission of LBP, headache or facial pain, cervical or neck pain, articular pain, and others. The small number of FMS diagnoses on admission may be related to some concerns, like the poor knowledge among physicians about FMS or real scepticism in the medical community regarding this syndrome and its related conditions [15][16][17]. Nevertheless, the systematic application of the 2016 ACR revised diagnostic criteria for FMS to these patients after the clinical evaluation outside the examination room highlighted a prevalence of positive criteria for FMS in 57 patients (20.3%).…”
Section: Discussionmentioning
confidence: 99%
“…We found support for findings related to younger participants experiencing dismissal on the assumption that they could not be dealing with such severe symptoms at their young age. 22 One participant also described racism leading to delays in her diagnosis due to lack of understanding of how symptoms present across diverse ethnic and racial populations. Notably, this article contributes to the literature on the damaging and potentially disabling impacts of stigmatization and invalidation among people living with chronic pain; participants highlighted how stigmatizations of FM at a systemic health care level can lead to internalization of these beliefs, resulting in self-judgment and risk of self-stigmatization in the individual, potentially leading to negative mental health consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Informers reported that only people who suffer from FMS understand it, remarking on the general lack of comprehension of relatives and healthcare professionals. A recent study about the experience of healthcare services for FMS in Sweden indicated that more than half of the sample felt misunderstood by the personnel and were missing an adequate treatment strategy [ 47 ].…”
Section: Discussionmentioning
confidence: 99%